2012
DOI: 10.5946/ce.2012.45.3.299
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Papillary Large Balloon Dilation: Guidelines for Pursuing Zero Mortality

Abstract: Since endoscopic papillary large balloon dilation (EPLBD) is used to treat benign disease and as a substitute for conventional methods, such as endoscopic sphincterotomy plus endoscopic mechanical lithotripsy, we should aim for zero mortality. This review defines EPLBD and suggests guidelines for its use based on a review of published articles and our large-scale multicenter retrospective review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…17 The balloon should always be inflated slowly and gradually, starting from a smaller diameter than the intended maximal target, to recognize obscure bile duct strictures with attention paid to the balloon shape under fluoroscopy. 44 3.3. The usual duration of balloon dilation is approximately 30 to 60 seconds after disappearance of the waist.…”
Section: The Balloon Should Be Inflated Slowly In Gradual Stepsmentioning
confidence: 99%
See 1 more Smart Citation
“…17 The balloon should always be inflated slowly and gradually, starting from a smaller diameter than the intended maximal target, to recognize obscure bile duct strictures with attention paid to the balloon shape under fluoroscopy. 44 3.3. The usual duration of balloon dilation is approximately 30 to 60 seconds after disappearance of the waist.…”
Section: The Balloon Should Be Inflated Slowly In Gradual Stepsmentioning
confidence: 99%
“…The speed and degree of balloon inflation should be carefully controlled to avoid adverse events in view of such obscure strictures of the distal bile duct. 44 If there is a suspicion of distal bile duct strictures during ERCP, especially in patients with a tapered distal bile duct, use of the pulling method of a large inflated retrieval balloon through the suspected site is recommended to confirm a suspected existence. 18 The risk of bleeding with EST depends on the extent of the ampullary incision and underlying conditions such as coagulopathy, use of antithrombotic and antiplatelet medications, cirrhosis, thrombocytopenia, and chronic renal failure.…”
Section: 4mentioning
confidence: 99%
“…Theoretically, radial force exerted around the surface of the balloon can cause the weakest region of the ampullary mucosa to rupture during the balloon manipulation. For successful EPLBD, proper ballooning size and gradual, cautious dilation are of the utmost importance [32]. …”
Section: Discussionmentioning
confidence: 99%
“…According to the reports [1][2][3][4][5][6][7][8][9], the success rate of CBD stone clearance was similar in EPLBD compared to EST alone. Mechanical use was less frequent in EPLBD, although mechanical usage in large stones was similar.…”
Section: Open Accessmentioning
confidence: 99%
“…Since then, several studies of EPLBD [2][3][4][5][6][7][8][9] for treatment of difficult bile duct stones have reported favorable outcomes and acceptable complication rates. In addition, a recent meta-analysis [10] reported that EPLBD should be considered as an alternative for patients in whom EST could not be routinely performed; it was also recommended for removal of large or difficult common bile duct stones in patients with an underlying coagulopathy or need for anticoagulation following endoscopic retrograde cholangiopancreatography (ERCP) because cases of hemorrhage in EPLBD are fewer than in EST.…”
Section: Introductionmentioning
confidence: 99%